Photovoltaic cell and method of manufacturing the same, stacked cell, photovoltaic module
Patent Information
- Application Number
- CN202611055690.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-27
AI Technical Summary
成熟的金属化工艺主要是以银浆为原料,但是银材料成本高昂且储量有限,成为制约进一步降本的主要瓶颈
本申请的光伏电池制备时,导电浆料中含有改性镍粉,由于改性镍粉表面中的镍磷合金层中含有磷元素,磷元素可以降低后续烧结过程中硅镍的共晶温度,因此可以保证导电浆料在较低的温度下就能实现烧结,不容易对基底产生严重的热损伤,从而使得制得的光伏电池仍然具有良好的输出功率。
Smart Images

Figure CN122995333A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic technology, and in particular to a photovoltaic cell and its preparation method, a tandem cell, and a photovoltaic module. Background Technology
[0002] In the fabrication of photovoltaic cells, a metallization process is required to create electrodes, thereby forming an ohmic contact between the two ends of the PN junction to achieve current output. Mature metallization processes primarily use silver paste as a raw material; however, the high cost and limited reserves of silver have become a major bottleneck restricting further cost reduction. While there are currently technical solutions using other materials to replace silver powder to reduce costs, these often result in poor sintering effects, leading to reduced output power of the photovoltaic cells. Summary of the Invention
[0003] This application provides a photovoltaic cell and its preparation method, a tandem cell, and a photovoltaic module, which at least helps to reduce the preparation cost while ensuring that the photovoltaic cell still has good output power.
[0004] The first aspect of this application provides a method for preparing a photovoltaic cell, comprising obtaining a substrate; coating a conductive paste on the surface of the substrate, the conductive paste comprising 60% to 75% conductive phase by mass fraction, the conductive phase comprising modified nickel powder, the modified nickel powder comprising nickel particles, the surface of the nickel particles being coated with a nickel-phosphorus alloy layer; and curing the conductive paste to form an electrode.
[0005] In one possible implementation, the particle size of the modified nickel powder is 100 nm to 500 nm.
[0006] In one possible implementation, the phosphorus content is 2% to 5% by mass, based on the mass of the nickel-phosphorus alloy layer.
[0007] In one possible implementation, the thickness of the nickel-phosphorus alloy layer is 2 nm to 10 nm.
[0008] In one possible implementation, electroless plating forms modified nickel powder, wherein the electroless plating solution includes nickel salts and a reducing agent, the reducing agent including sodium hypophosphite.
[0009] In one possible implementation, the conductive paste includes 1% to 5% of an initiator by mass fraction; the initiator includes metal powder with a melting point not higher than 350°C.
[0010] In one possible implementation, the metal powder includes at least one of bismuth powder, indium powder, or tin powder.
[0011] In one possible implementation, the particle size of the metal powder is 5 nm to 100 nm.
[0012] In one possible implementation, the conductive paste, by mass fraction, also includes: 2% to 6% glass powder and 18% to 32% organic carrier.
[0013] In one possible implementation, the curing process includes: drying the conductive paste; sintering the dried conductive paste using a laser; and applying a reverse bias voltage.
[0014] Secondly, this application provides a photovoltaic cell, which is prepared by the above-described photovoltaic cell preparation method; the photovoltaic cell includes a substrate, and electrodes are disposed on the surface of the substrate.
[0015] Thirdly, this application provides a tandem solar cell, comprising: a crystalline silicon bottom cell, which is a photovoltaic cell according to the second aspect; and a perovskite top cell, which is located on one side of the bottom cell.
[0016] Fourthly, this application provides a photovoltaic module, including a battery string, the battery string including a plurality of second-side photovoltaic cells or third-side stacked cells arranged along a first direction, and the plurality of battery strings are also arranged along a second direction; a solder strip, the solder strip extending along the first direction and arranged along the second direction, the solder strip being used to connect two adjacent photovoltaic cells along the first direction; and a backsheet, the backsheet being located on the side of the solder strip away from the back of the battery string.
[0017] The technical solution provided in this application has at least the following advantages: In the preparation of the photovoltaic cell of this application, the conductive paste contains modified nickel powder. Since the nickel-phosphorus alloy layer on the surface of the modified nickel powder contains phosphorus, the phosphorus can reduce the eutectic temperature of silicon and nickel in the subsequent sintering process. Therefore, the conductive paste can be sintered at a lower temperature, which is less likely to cause serious thermal damage to the substrate, so that the photovoltaic cell still has good output power. Attached Figure Description
[0018] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a process flow diagram of the photovoltaic cell fabrication of this application; Figure 2 This is a schematic diagram of the structure of the photovoltaic cell in this application; Figure 3 This is a schematic diagram of the structure of the photovoltaic module in the embodiments of this application.
[0020] Reference numerals: 01-substrate; 02-electrode; 100-cell string; 101-cell; 111-welding strip; 120-backsheet. Detailed Implementation
[0021] As mentioned in the background section, to reduce manufacturing costs, there are currently technical solutions that use other materials to replace silver powder. However, these solutions often result in poor sintering effects, leading to reduced output power of photovoltaic cells. For example, the Ni / Cu electroplating technology typically requires removing the silicon nitride layer first through laser grooving. This process can easily cause thermal damage to the silicon substrate, leading to open-circuit voltage (Voc) loss. Furthermore, the nickel-silicon alloying after electroplating usually relies on traditional low-temperature sintering furnaces for heat treatment. Furnace tube sintering suffers from uneven temperature field distribution, easily leading to large differences in contact resistance in different areas of the cell, affecting module consistency. Another example is the research attempting to use base metal nickel to replace part of the silver powder in the slurry, or to use laser-induced sintering technology alone to treat the electroplated nickel layer. However, how to deeply integrate slurry formulation design with laser processing, reduce dependence on sintering temperature through functional components in the slurry, repair laser damage, and achieve ultra-uniform contact remains a pressing technical challenge in this field.
[0022] This application provides a method for preparing a photovoltaic cell. In this method, modified nickel powder is used as the main component of the conductive paste. The conductive paste has a low sintering temperature but still has a good sintering effect, and can well replace silver powder.
[0023] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined. Similarly, "multiple sets" refers to two or more sets (including two sets), and "multiple pieces" refers to two or more pieces (including two pieces).
[0024] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0025] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.
[0026] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application. For example, if the device or element in the illustration is inverted, then the element described as "below," "under," "below," or "bottom" of other elements or features will be oriented "above" or "top" of other elements or features. Therefore, the term "below" may cover both above and below orientation depending on the context in which the term is used, which will be obvious to those skilled in the art. Materials may be oriented in other ways (e.g., rotated 90 degrees, inverted, flipped), and the spatial relative descriptive terms used herein may be interpreted accordingly.
[0027] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0028] In the description of embodiments of this application, the terms "about," "approximately," "roughly," or "about" for referring to a specific parameter include numerical values, and those skilled in the art will understand that the deviation from the numerical value is within the acceptable tolerance of the specific parameter. For example, "about" or "about" for a numerical value may include additional numerical values that are in the range of 90.0% to 110.0% of the numerical value, such as in the range of 95.0% to 105.0%, 97.5% to 102.5%, 99.0% to 101.0%, 99.5% to 100.5%, or 99.9% to 100.1%.
[0029] In the accompanying drawings corresponding to the embodiments of this application, the thickness and / or area of layers, films, panels, regions, etc., are enlarged for better understanding and ease of description. Throughout the specification, the same reference numerals denote the same elements. Furthermore, when describing a component as being "generally" formed on another component, it means that the component is not formed on the entire surface (or front surface) of the other component, nor is it formed on a portion of the edge of the entire surface.
[0030] In the description of embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and may be further included. When describing a component (such as a layer, film, region, or substrate) on or on the surface of another component, the component may be "directly" located on the surface of the other component, or there may be an intermediate component between the two components. Conversely, when describing a component on the surface of another component, or a component "directly" on another component, or a component surface on which another component is formed or disposed, it indicates that there is no intermediate component between the two components. For simplicity and clarity, various components may be drawn at any scale. In the drawings, some components may be omitted for simplicity.
[0031] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "component" is also intended to include the plural form unless the context clearly indicates otherwise.
[0032] The “components” mentioned above can refer to layers, membranes, regions, parts, plates, or structures, etc.
[0033] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.
[0034] The process flow diagram for the fabrication of photovoltaic cells in this application is as follows: Figure 1 As shown, the specific steps include the following: S100, Obtain the substrate.
[0035] In this step, the substrate is a solar cell without electrodes. This application does not have specific requirements for the type of solar cell, as long as it meets the purpose of this application. For example, the type of solar cell may include, but is not limited to, at least one of PERC solar cells (PERC stands for Passivated Emitter Rear Cell), TOPcon solar cells (TOPcon stands for Tunnel Oxide Passivated Contact), bulk heterojunction solar cells, and BC solar cells (BC stands for Back Contact). The preparation method of this application is particularly applicable to TOPCon solar cells, so in the embodiments of this application, TOPCon solar cells will be used as an example for specific description.
[0036] Typically, the substrate contains a PN junction and a passivation layer on the surface. The conductive paste then etches the passivation layer and forms an electrode that makes an ohmic contact with the PN junction, thereby collecting and discharging current.
[0037] S200. Obtain a conductive paste, which, by mass fraction, includes 60% to 75% conductive phase, the conductive phase including modified nickel powder, the modified nickel powder including nickel particles, and the surface of the nickel particles being coated with a nickel-phosphorus alloy layer.
[0038] In this step, the conductive paste will be sintered to form electrodes, and the conductive phase ensures that the formed electrodes can collect current. Because the nickel-phosphorus alloy layer on the surface of the modified nickel powder contains phosphorus, phosphorus can lower the eutectic temperature of silicon and nickel during the subsequent sintering process. Therefore, the conductive paste can be sintered at a lower temperature, which is less likely to cause serious thermal damage to the substrate, thus ensuring that the photovoltaic cell still has good output power.
[0039] This application does not have specific requirements for the particle size of the modified nickel powder, as long as it meets the purpose of this application. As an example, in some embodiments of this application, the particle size of the modified nickel powder is 100nm~500nm, specifically 100nm, 120nm, 170nm, 200nm, 230nm, 290nm, 310nm, 370nm, 400nm, 410nm, 470nm, 500nm, etc., or within a range consisting of any two of the above values. Furthermore, since the modified nickel powder includes nickel particles and a nickel-phosphorus alloy layer, in this application, the "particle size of the modified nickel powder" refers to the particle size of the secondary particles, that is, the particle size includes the thickness of the nickel-phosphorus alloy layer.
[0040] In this application, the thickness of the nickel-phosphorus alloy layer is generally 2nm to 10nm, specifically 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, or within any range of two of the above values. This ensures a sufficient supply of phosphorus, effectively reducing the nickel-silicon eutectic temperature and promoting low-temperature sintering, while avoiding the adverse effects of an excessively thick alloy layer on the conductivity of the nickel powder. Simultaneously, this thickness allows phosphorus to diffuse uniformly to the interface during laser sintering, ensuring stable contact resistance, a wide process window, and facilitating consistent mass production.
[0041] In addition, in order to ensure that the electrode still has good conductivity while the sintering temperature is reduced, the mass content of phosphorus in the nickel-phosphorus alloy layer is usually set in the range of 2% to 5%, specifically 2%, 2.2%, 2.7%, 3%, 3.3%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or within any two of the above values.
[0042] Of course, in some other embodiments of this application, modified nickel powder can also be used in combination with silver powder to form a conductive phase together; this can also reduce the amount of silver powder used and reduce the preparation cost.
[0043] The modified nickel powder used in this application can be commercially available or prepared in-house; this application has no particular requirements in this regard, as long as it meets the purpose of this application. As an example, this application can use electroless plating to form the modified nickel powder. Electroless plating is a preparation method that does not require electricity and, based on the principle of redox reaction, uses a reducing agent in a solution containing metal ions to reduce metal ions to metal and deposit them on the surface of a material to form a coating. In this application, the electroless plating solution used includes nickel salts and a reducing agent. The nickel salts exist in the electroless plating solution in ionic form, and then, under the catalytic action of nickel particles, are reduced to nickel metal by the reducing agent and deposited on the surface of the nickel particles, thereby forming modified nickel powder. This application does not have any particular restrictions on the specific types of nickel salts and reducing agents, as long as they meet the purpose of this application. For example, the nickel salt can be nickel sulfate, nickel chloride, etc.; considering the subsequent formation of a nickel-phosphorus alloy layer, the reducing agent can be sodium hypophosphite (also known as "sodium hypophosphite", with the molecular formula NaPH2O2, usually prepared as a chemical plating solution using its hydrate). After reducing the nickel ions, phosphorus will also be displaced into the nickel lattice, forming a face-centered cubic supersaturated solid solution, thereby forming a nickel-phosphorus alloy layer. The specific preparation steps are as follows: nickel particles are placed in a chemical plating solution and reacted for 10 to 30 minutes, wherein the chemical plating solution includes nickel sulfate and sodium hypophosphite, the reaction temperature is generally 75℃ to 85℃, and the reaction pH is 8 to 10. Of course, other methods can also be used to prepare modified nickel powder, and this application does not impose any particular restrictions on this.
[0044] In addition, in some embodiments of this application, the conductive paste further includes 1% to 5% of an initiator by mass fraction; the initiator includes metal powder with a melting point not exceeding 350°C. The initiator has a low melting point (far lower than the melting point of nickel), allowing it to preferentially melt during subsequent curing. This fills the gaps between modified nickel powder particles and wets the substrate. The preferentially formed liquid phase of the initiator further enhances the sintering effect, significantly reducing the overall thermal budget required to achieve ohmic contact, which helps to further reduce thermal damage during sintering and improve the output power of the resulting photovoltaic cell. Specifically, in some embodiments of this application, the metal powder may include, but is not limited to, at least one of bismuth powder, indium powder, or tin powder. It should be noted that metal powders such as bismuth powder can be in alloy form or in elemental form; this application does not have special requirements in this regard, as long as the melting point of the metal powder is not higher than 350°C. Furthermore, in some embodiments of this application, to ensure that the initiator melts more rapidly, the particle size of the initiator is generally 5nm to 100nm.
[0045] In this step, the conductive paste includes components such as an organic carrier and glass powder, in addition to the conductive phase and the triggering agent. As an example, a detailed description follows.
[0046] Organic carriers generally serve to disperse the various components in conductive slurry and maintain the uniformity and stability of the conductive slurry system. Their dosage can be adjusted according to actual needs. For example, based on the mass of the conductive slurry, the mass content of organic carriers is 18% to 32%, specifically 18%, 20%, 23%, 25%, 28%, 30%, 32%, etc., or within any two of the above values.
[0047] Typically, organic carriers include organic solvents, organic resins, and additives. Organic solvents constitute the largest portion of the organic carrier, usually accounting for 92% to 96% of its total mass. Their purpose is to fully disperse or dissolve the components in the conductive paste; therefore, most of the organic carrier will volatilize or decompose during sintering. This application does not have specific requirements regarding the content and type of each component in the organic carrier, as long as it meets the purpose of this application. For example, organic solvents include, but are not limited to, at least one of terpineol, butyl carbitol, and dimethyl esters. Organic resins generally act as binders, giving the conductive paste a suitable viscosity to ensure that subsequent coating and printing steps can proceed normally. Types of organic resins include, but are not limited to, at least one of ethyl cellulose, acrylic resin, and rosin resin. Additives can be added according to actual needs to improve the corresponding performance of the conductive paste. For example, additives may include, but are not limited to, at least one of dispersants, thixotropic agents, and defoamers.
[0048] During sintering, the glass powder can penetrate the passivation film, ensuring that the electrode formed by subsequent sintering and solidification can form an ohmic contact with the substrate. This application does not particularly limit the type and content of the glass powder, as long as it meets the purpose of this application. As an example, based on the mass of the conductive paste, the mass content of the glass powder is 2% to 6%, specifically 2%, 3%, 4%, 5%, 6%, or within any two of the above values. The glass powder can be lead-containing glass powder or lead-free glass powder. Lead-containing glass powder has lower contact resistance, while lead-free glass powder is environmentally friendly. Specifically, in some embodiments of this application, lead-free glass powder of the bismuth borosilicate glass system is used, with a softening point of 380℃ to 450℃. The specific components, by mass fraction, include Bi2O3: 50% to 65%, B2O3: 10% to 20%, SiO2: 10% to 15%, ZnO: 5% to 10%, and the remainder being alkaline earth metal oxides. Of course, in other embodiments of this application, other lead-free glass powders can also be used, and this application does not particularly limit this.
[0049] This application does not have any special requirements for the preparation steps of the conductive paste. As an example, this application will briefly describe the preparation of the conductive paste: S210, prepare organic carrier.
[0050] This step typically involves dissolving the organic resin (such as ethyl cellulose or acrylic resin) in an organic solvent, adding the additives, then heating in a water bath and stirring until completely dissolved, and finally filtering for later use. The organic solvent is usually a mixture of terpineol and butyl carbitol, and the water bath heating temperature is generally between 60°C and 80°C.
[0051] S220. The modified nickel powder, triggering agent and glass powder are mixed evenly to form a mixed powder.
[0052] In this step, the three components are usually mixed and then a small amount of surfactant (such as lecithin) is added for dry ball milling. This allows the triggering agent to be uniformly adsorbed on the surface of the modified nickel powder, preventing the modified nickel powder from agglomerating. The ball milling time is usually 2 to 4 hours.
[0053] S230. The mixed powder is mixed with an organic carrier and rolled to form an initial slurry.
[0054] In this step, the rolling pressure is generally gradually increased to 0.5MPa, and then cyclicated 5 to 8 times. This ensures that the fineness of the initial slurry is ≤10μm, so that the screen is not easily clogged during the subsequent coating process.
[0055] S240. Vacuum degassing is performed on the initial slurry to obtain a conductive slurry.
[0056] In this step, the initial paste is usually placed in a vacuum degassing machine and degassed at -0.1MPa for 30 to 60 minutes. This removes the gas from the paste, thereby reducing printing defects and poor sintering.
[0057] It should be noted that the order of steps S210 and S220 in the preparation of the conductive paste is not particularly required. The organic carrier can be prepared first, or the mixed powder can be formed first. In addition, other methods can be used to prepare the conductive paste, and the types, contents and processing parameters of raw materials can be adjusted according to actual needs. This application does not have any special requirements in this regard, as long as the purpose of this application is met.
[0058] S300: Coat the surface of the substrate with a conductive paste.
[0059] In this step, conductive paste is typically applied to the surface of the substrate through printing. This application does not impose any particular restrictions on printing parameters, such as the amount used, squeegee pressure, printing speed, and screen tension; these can be adjusted according to actual needs, as long as the purpose of this application is met. For example, the wet weight can be controlled at 0.15g / sheet to 0.25g / sheet during printing.
[0060] S400: The conductive paste is cured to form an electrode.
[0061] In this step, the curing process allows the conductive paste to form electrodes, which are electrically connected to the substrate, thus collecting current. Because the conductive paste contains modified nickel powder as a conductive phase, and the surface of the modified nickel powder has a nickel-phosphorus alloy layer, the phosphorus element can lower the eutectic temperature of silicon-nickel. Therefore, maintaining a low curing temperature allows the conductive paste and substrate to solidify and form ohmic contacts, thus forming electrodes. Low temperatures minimize the risk of severe thermal damage to the substrate, ensuring the resulting photovoltaic cell still has good output power. Furthermore, if the conductive paste contains metal powder as a trigger, the metal powder will melt first during curing to form a liquid phase, filling the micropores of the substrate and the gaps between the modified nickel powder, and achieving the effect of etching the passivation layer. This reduces the overall thermal budget required to achieve ohmic contacts, further reducing thermal damage during sintering and improving the output power of the resulting photovoltaic cell.
[0062] As an example, in this step, the curing process generally involves first drying the conductive slurry, then using a laser to sinter the dried conductive slurry, and applying a reverse bias voltage.
[0063] Specifically, drying the conductive paste removes most of the organic carrier (mainly organic solvents), forming a dry film layer to ensure proper sintering of the subsequent conductive paste. In this step, the drying temperature of the conductive paste is generally 150℃~200℃, the drying time is generally 3min~5min, and the drying is generally carried out in a chain drying oven.
[0064] When sintering dried conductive paste using a laser, the laser heats the paste, causing it to melt and etch the passivation layer. This melts the paste and forms a nickel-silicon alloy phase with the substrate, achieving ohmic contact. In some embodiments of this application, the presence of a triggering agent in the conductive paste widens the laser sintering temperature window, preventing damage to the silicon substrate due to localized overheating. Simultaneously, the laser's point-scanning characteristics ensure that the contact resistance uniformity of the entire cell fluctuates by less than 0.5Ω. Furthermore, the triggering agent preferentially melts to form a liquid phase. The Joule heating effect induced by the applied reverse bias voltage promotes further diffusion of modified nickel powder into the substrate through the liquid phase channels, which is more conducive to the in-situ formation of a nickel-silicon alloy phase at the interface at low temperatures, achieving ohmic contact.
[0065] This application does not have specific requirements for the parameters of laser drying of conductive slurry and the parameters of reverse bias voltage. These parameters can be adjusted according to actual needs, as long as they meet the purpose of this application. As an example, in some embodiments of this application, a continuous or pulsed infrared laser (wavelength 1064nm±50nm) can be used for scanning sintering. The laser power is 30W~60W, the scanning speed is 10m / s~25m / s, the spot diameter is 30μm~80μm, and the sintering atmosphere can be air or nitrogen environment; the reverse bias voltage can be a DC voltage of 5V~15V.
[0066] On the other hand, this application also provides a photovoltaic cell, which is prepared by the above-described method, and its structural schematic diagram is shown below. Figure 2 As shown. The photovoltaic cell of this application embodiment includes a substrate 01, and an electrode 02 is disposed on the surface of the substrate 01. An electrical connection is formed between the electrode 02 and the substrate 01. The electrode 02 is formed by curing a conductive paste.
[0067] It should be noted that the substrate 01 in this application often includes multiple layers such as a PN junction and a passivation layer. Figure 2 While not explicitly shown, those skilled in the art can adjust it according to actual needs; further details are omitted here. Additionally, Figure 2 This explanation uses TOPCon solar cells as an example only. Schematic diagrams of other types of solar cells, such as BC cells, are not provided. Figure 2 Although they are different, the electrodes 02 are all formed by curing the conductive paste in step S100.
[0068] This application also provides a tandem solar cell, including a crystalline silicon bottom cell and a perovskite top cell, wherein the perovskite top cell is located on one side of the crystalline silicon bottom cell, and the crystalline silicon bottom cell is the aforementioned photovoltaic cell.
[0069] In addition, such as Figure 3 As shown, this application also provides a photovoltaic module, including a battery string 100, a solder ribbon 111, and a backsheet 120. The battery string 100 includes a plurality of battery cells 101 arranged along a first direction X. The battery cells 101 include the photovoltaic cells described above or the stacked cells described above, and the plurality of battery strings are also arranged along a second direction Y. The solder ribbon extends along the first direction X and is arranged along the second direction Y. The solder ribbon 111 is used to connect two adjacent battery cells 101 along the first direction X. The backsheet 120 is located on the side of the solder ribbon 111 away from the back of the battery string 100.
[0070] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0071] Example 1 This embodiment provides a photovoltaic cell, the specific preparation method of which is as follows: TOPCon solar cells were used as the substrate.
[0072] A conductive paste was obtained, comprising, by mass fraction, 68% conductive phase modified nickel powder, 3% trigger bismuth powder, 25% organic carrier, and 4% glass powder. The modified nickel powder has an average particle size of 300 nm and consists of nickel particles coated with a nickel-phosphorus alloy layer. The phosphorus content of the nickel-phosphorus alloy layer is 2%, and the thickness of the nickel-phosphorus alloy layer is 6 nm. The bismuth powder has an average particle size of 80 nm.
[0073] A conductive paste is coated on the surface of the TOPCon solar cell.
[0074] The conductive paste was dried at 180°C for 4 minutes. Afterwards, the dried conductive paste was sintered using a laser while a reverse bias voltage was applied.
[0075] Example 2 This embodiment provides a photovoltaic cell, the main difference of which is that the conductive paste, by mass fraction, includes 60% conductive phase modified nickel powder, 2% trigger bismuth powder, 32% organic carrier, and 6% glass powder.
[0076] Example 3 This embodiment provides a photovoltaic cell whose preparation method differs from that of Embodiment 1 in that the conductive paste, by mass fraction, includes 75% conductive phase modified nickel powder, 5% trigger bismuth powder, 18% organic carrier, and 2% glass powder.
[0077] Example 4 This embodiment provides a photovoltaic cell, the main difference of which is that the modified nickel powder contains 5% phosphorus in the surface nickel-phosphorus alloy layer compared to the method of preparation in embodiment 1.
[0078] Example 5 This embodiment provides a photovoltaic cell whose preparation method differs from that of Embodiment 1 in that the thickness of the nickel-phosphorus alloy layer on the surface of the modified nickel powder is 2 nm.
[0079] Example 6 This embodiment provides a photovoltaic cell, the main difference of which compared to the preparation method of Embodiment 1 is that the thickness of the nickel-phosphorus alloy layer on the surface of the modified nickel powder is 10 nm.
[0080] Example 7 This embodiment provides a photovoltaic cell whose preparation method differs from that of Embodiment 1 in that the average particle size of the modified nickel powder is 100 nm.
[0081] Example 8 This embodiment provides a photovoltaic cell whose preparation method differs from that of Embodiment 1 in that the average particle size of the modified nickel powder is 500 nm.
[0082] Example 9 This embodiment provides a photovoltaic cell, the main difference in its preparation method compared to Embodiment 1 being that: the conductive paste, by mass fraction, includes 68% conductive phase modified nickel powder, 28% organic carrier, and 4% glass powder. The average particle size of the modified nickel powder is 300 nm; the modified nickel powder comprises nickel particles, the surface of which is coated with a nickel-phosphorus alloy layer, the phosphorus content in the nickel-phosphorus alloy layer being 2%.
[0083] Comparative Example 1 This comparative example provides a method for preparing a photovoltaic cell. Compared to Example 1, nickel powder with an average particle size of 300 nm is used instead of modified nickel powder in the conductive slurry. When sintering the dried conductive slurry using a laser, the laser power needs to be increased to complete the sintering.
[0084] Comparative Example 2 This comparative example provides a method for preparing a photovoltaic cell. The main difference from Example 1 is that the conductive paste, by mass fraction, includes 59% conductive phase modified nickel powder, 3% trigger bismuth powder, 34% organic carrier, and 4% glass powder.
[0085] Comparative Example 3 This comparative example provides a method for preparing a photovoltaic cell. The main difference from Example 1 is that the conductive paste, by mass fraction, includes 76% conductive phase modified nickel powder, 3% trigger bismuth powder, 18% organic carrier, and 3% glass powder.
[0086] Test methods and equipment Contact resistance uniformity test The Transmission Line Method (TLM) was used for testing. The standard T / CPIA 0051-2023, "Test Method for Contact Resistivity of Metal Electrodes in Crystalline Silicon Photovoltaic Cells: Transmission Line Method (TLM)," was followed.
[0087] The test was conducted using a TLM contact resistance tester, and the specific test steps included: 1. Take the sintered finished battery cell and cut it into test strips with a width of 4mm~10mm and a length of not less than 230mm along the vertical direction of the grid line; 2. Fix the test strip onto the vacuum adsorption device of the TLM test platform; 3. Use the four-probe method or TLM method to measure the total resistance between electrode pairs with different spacings; 4. Extract the contact resistivity (μΩ) through linear fitting, and perform multi-point measurements at no less than 5 different locations on the surface of the solar cell; 5. Calculate the difference between the maximum and minimum contact resistivity at each measuring point, and use it as an evaluation index for the uniformity of contact resistance.
[0088] Output power test Referring to IEC 60904-1 standard "Photovoltaic devices - Part 1: Measurement of photovoltaic current-voltage characteristics", under standard test conditions (STC: irradiance 1000W / m²), 2 Tested at battery temperature 25℃ (AM1.5 spectrum).
[0089] Test equipment: AAA-grade solar simulator, IV test system, standard reference cell (for irradiance calibration), and temperature control system.
[0090] Test steps: 1. Place the battery cells on a temperature control test bench and stabilize the temperature at 25℃±1℃; 2. Calibrate the solar simulator's irradiance to 1000 W / m using a standard reference cell. 2 ; 3. Make contact between the front electrode of the solar cell and the probe array of the IV testing system to ensure good contact; 4. Turn on the solar simulator and irradiate the solar cells; 5. The IV testing system automatically scans the current-voltage characteristic curve of the solar cell and records the short-circuit current (IV). sc ), open circuit voltage (V) oc ), maximum power point power (P) max Parameters such as ) 6. According to P max Calculate the conversion efficiency η, η = P max / (irradiance × battery area) × 100%.
[0091] The test results are shown in Table 1.
[0092] Table 1
[0093] As can be seen from the above, in the embodiments of this application, the modified nickel powder in the conductive paste can effectively reduce the sintering temperature while the sintering effect is basically unaffected, thus significantly reducing the occurrence of substrate damage. In particular, as shown in Examples 1 and 8, when the conductive paste contains a triggering agent such as bismuth powder, the sintering temperature can be further reduced, ensuring that the output power of the resulting solar cell is higher.
[0094] Furthermore, as shown in Example 1 and Comparative Example 1, while using unmodified nickel powder in conductive paste can reduce costs, it significantly impacts the output power of the solar cells. Examples 1 and Comparative Examples 1-2 demonstrate that the modified nickel powder content in the conductive paste needs to be controlled within the range of 60% to 75%. Too much nickel powder can introduce excess phosphorus, reducing output power; too little nickel powder will prevent the sintering temperature from being effectively reduced, leaving the substrate easily damaged and also reducing output power.
[0095] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.
Claims
1. A method for preparing a photovoltaic cell, characterized in that, include: Obtain the base; A conductive paste is coated on the surface of the substrate. The conductive paste comprises 60% to 75% conductive phase by mass fraction. The conductive phase includes modified nickel powder, which comprises nickel particles. The surface of the nickel particles is coated with a nickel-phosphorus alloy layer. The conductive paste is cured to form an electrode.
2. The method for preparing a photovoltaic cell according to claim 1, characterized in that, The modified nickel powder has a particle size of 100nm~500nm.
3. The method for preparing a photovoltaic cell according to claim 1, characterized in that, Based on the mass of the nickel-phosphorus alloy layer, the mass content of phosphorus is 2% to 5%.
4. The method for preparing a photovoltaic cell according to claim 1, characterized in that, The thickness of the nickel-phosphorus alloy layer is 2nm~10nm.
5. The method for preparing a photovoltaic cell according to claim 1, characterized in that, The modified nickel powder is formed by electroless plating, wherein the electroless plating solution includes nickel salt and a reducing agent, and the reducing agent includes sodium hypophosphite.
6. The method for preparing a photovoltaic cell according to claim 1, characterized in that, The conductive paste includes 1% to 5% triggering agent by mass fraction; the triggering agent includes metal powder, and the melting point of the metal powder is not higher than 350°C.
7. The method for preparing a photovoltaic cell according to claim 6, characterized in that, The metal powder includes at least one of bismuth powder, indium powder, or tin powder.
8. The method for preparing a photovoltaic cell according to claim 6 or 7, characterized in that, The particle size of the metal powder is 5nm~100nm.
9. The method for preparing a photovoltaic cell according to any one of claims 1 to 7, characterized in that, The conductive paste, by mass fraction, also includes: 2%~6% glass powder and 18%~32% organic carrier.
10. The method for preparing a photovoltaic cell according to claim 1, characterized in that, The curing process includes: Dry the conductive paste; The dried conductive paste is sintered using a laser, and a reverse bias voltage is applied.
11. A photovoltaic cell, characterized in that, The photovoltaic cell is prepared by the method of any one of claims 1 to 10; the photovoltaic cell includes a substrate, and electrodes are disposed on the surface of the substrate.
12. A stacked battery, characterized in that, include: A crystalline silicon base cell, wherein the crystalline silicon base cell is the photovoltaic cell as described in claim 11; A perovskite top cell, wherein the perovskite top cell is located on one side of the bottom cell.
13. A photovoltaic module, characterized in that, The battery string includes a plurality of photovoltaic cells as described in claim 11 or tandem cells as described in claim 12 arranged along a first direction, and the plurality of battery strings are further arranged along a second direction; A solder strip, which extends along a first direction and is arranged along a second direction, and is used to connect two adjacent photovoltaic cells and / or stacked cells along the first direction; A backplate, located on the side of the solder strip away from the back of the battery string.